2020
DOI: 10.34117/bjdv6n9-297
|View full text |Cite
|
Sign up to set email alerts
|

Biomarcadores Histológicos Em Brânquias De Peixes Na Avaliação Da Contaminação Ambiental Do Rio Mearim, Nordeste Brasileiro / Histological Biomarkers in Fish Gills in the Assessment of Environmental Contamination of the Mearim River, Northeastern Brazil

Abstract: Biomarcadores histológicos em brânquias de peixes na avaliação da contaminação ambiental do Rio Mearim, Nordeste brasileiro Histological biomarkers in fish gills in the assessment of environmental contamination of the Mearim river, Northeastern Brazil

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…According to Soares et al (2020) identified lamellar fusion and epithelial displacement in the tissues of S. herzbergii sampled in São Marcos Bay. Lamellar fusion is a type of injury that occurs as a defense mechanism against direct contact between contaminants and the lamellar epithelium; however, these changes also reduce the respiratory surface, which may result in death (Pereira et al, 2020). According to Pereira et al (2020), epithelial displacement is one of the most common biomarkers observed in the gills of fish exposed to acute toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Soares et al (2020) identified lamellar fusion and epithelial displacement in the tissues of S. herzbergii sampled in São Marcos Bay. Lamellar fusion is a type of injury that occurs as a defense mechanism against direct contact between contaminants and the lamellar epithelium; however, these changes also reduce the respiratory surface, which may result in death (Pereira et al, 2020). According to Pereira et al (2020), epithelial displacement is one of the most common biomarkers observed in the gills of fish exposed to acute toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Lamellar fusion is a type of injury that occurs as a defense mechanism against direct contact between contaminants and the lamellar epithelium; however, these changes also reduce the respiratory surface, which may result in death (Pereira et al, 2020). According to Pereira et al (2020), epithelial displacement is one of the most common biomarkers observed in the gills of fish exposed to acute toxicity. The authors argued that fusion of secondary lamellae is also frequently found in organisms affected by contaminants.…”
Section: Discussionmentioning
confidence: 99%